Compromiso laboral y sus efectos en la gestión administrativa de la empresa KONICA en la ciudad de Babahoyo periodo 2023. - Candelario Vera, Brenda Valeria (2024)
The company Konica is dedicated to the commercialization of products such as photographic sessions, photographic prints, personalized gifts, in the city of Babahoyo. Currently, the company has presented problems regarding the labor commitment of its collaborators, since there is little opportunity for personal development and little publicity. These problems arise because the company has poorly organized and unmotivated personnel, which is reflected in the administrative management of the company. The objective of this study is to analyze the effects of labor commitment in the administrative management of the company Konica in the city of Babahoyo period 2023. The results of the survey allowed to recognize that there is low labor performance due to several factors among them the most representative, the failure to establish goals and objectives, has prevented the company to grow and face challenges and be competitive in the market. The conclusion is that the work commitment of Konica's work team is deficient, due to the non-implementation of actions that allow the optimization of their responsibility with the company. The staff is not committed to the company because their responsibilities have not been clearly established, therefore they have been limited in the fulfillment of their activities. The staff lacks commitment to the company because their responsibilities have not been clearly established, these factors have limited the work team in the fulfillment of its activities. The work team does not show a greater effort in carrying out the tasks because it is not constantly evaluated to identify shortcomings or enhance its strengths. At the end, strategies are presented to solve the problem studied.